Which White Wire? A Multi-centre Randomised Controlled Trial on Alignment Efficiency and Colour Performance - Esmail, Zaid; Ulhaq, Aman; Kamaruddin, Anis Farhan; Bister, Dirk; Sherriff, Martyn (2015)
AIMS: To evaluate the alignment efficiency and colour performance of four coated nickel-titanium aligning archwires over an eight-week period. The aim was to establish whether the latest aesthetic archwires have dispelled their reputation. SUBJECTS AND METHOD: One hundred and twenty participants requiring fixed appliance orthodontic treatment had each dental arch randomly allocated to one of four interventions: (1) Forestadent® BioCosmetic® 0.017 inch (2) Forestadent® Titanol® Cosmetic 0.016 inch (3) TP Orthodontics Aesthetic 0.014 inch (4) Ortho Organizers® Tooth Tone® 0.016 inch. The archwires were ligated and remained in situ for an eight week period. Changes in Little's Irregularity Index were measured on dental casts using digital callipers and retrieved archwires were measured for colour change (ΔE) and coating loss. Colour assessments were made using digital photography and Adobe® Photoshop®, with ΔE values computed using the CIE L*a*b* system. Coating loss was measured by analysing digitally scanned images and using Autodesk® AutoCAD®. RESULTS: One hundred and nineteen patients (74 females, 45 males) completed the trial. Significant alignment was achieved in all groups, however, one-way ANOVA showed no difference in alignment efficiency among the four groups. All four archwires showed significant mean colour change and coating loss after clinical use. One-way ANOVA showed a statistically significant difference between the archwires for ΔE (P = 0.001), with Titanol Cosmetic showing the greatest statistically significant colour change. There was no statistically significant difference between the archwires for coating loss. CONCLUSION: There was no difference in alignment efficiency amongst the coated archwires used, however there was appreciable colour change and coating loss after clinical use of coated aligning archwires. The aesthetic properties of these coated archwires are not ideal.